(3JPcQI GdChdjGAs - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO COjS GdbQfj (B- (3GdecQe CHh YHO Gddg eMeO Hf GOQjS GdTGaYj Gdecj Hbhd aj eSfOI eG dGjMb cKQI GNHQfG GdeGd s
(3BNQgG (B:s
(3bGd QCjJ GdTjN GHGSYjO QMeg Gddg aj GdefGe abdJ eG aYd Gddg Hc bGd cGf GdGeQ GSgd aeG XffG s
(3HgG fXGe GdJYbjHIs
(3hHChdg agQSs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B57s
Keywords: (3eJaQbGJs